1980
DOI: 10.21273/jashs.105.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Eight Crabapples by Pollen Surface Sculpture1

Abstract: Pollen specimens from 8 ornamental crabapples (Malus spp.) were compared using the scanning electron microscope (SEM) to determine if they, like apple cultivars, can be distinguished by pollen characters. All pollen grains were approximately equivalent in size, tricolpate, elliptical in shape, with tectate-perforate exine type. Exine riding was superficially similar among all 8 crabapples, but close examination revealed sufficient detail to distinguish between them. Pollen from 4 of the 8 crabapples, M. baccat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Further characteristics of exine topography, such as pit and ridge shape, as demonstrated by Mass (4), Foggle (2, 3), and Martens and Fretz (6), may be utilized to classify species and cultivars; although in many cultivars such traits appear very similar. Grant (11) for instance, was unable to distinguish between subspecies of Zea mays on the basis of wall sculpture alone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further characteristics of exine topography, such as pit and ridge shape, as demonstrated by Mass (4), Foggle (2, 3), and Martens and Fretz (6), may be utilized to classify species and cultivars; although in many cultivars such traits appear very similar. Grant (11) for instance, was unable to distinguish between subspecies of Zea mays on the basis of wall sculpture alone.…”
Section: Resultsmentioning
confidence: 99%
“…Reports of the effects of summer pruning on apple trees are varied. Summer pruning has been reported to reduce ( 1 ,7 , 17), to increase (8,12) growth (6,8) compared to dormant-pruned or unpruned controls. Utermark (20) reported that summer pruning reduced tree size, but Marini and Barden (12) concluded that summer pruning compared to similar dormant pruning could not control vegetative growth due to its stimulation of shoot growth in the following year.…”
Section: The Influence Of Summer Pruning and Cropping On Growth And F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Pollen morphology, sculpturing, and structure are useful in taxonomic studies from the family to the cultivar level (8,11,16,25). In this study, SEM was employed to determine if pollen grain morphology and structure could be employed to identify 'Received for publication June 19, 1981. This study was partially funded by a Statewide Critical Applied R e s e a r c h g r a n t t o th e s e c o n d a u t h o r .…”
mentioning
confidence: 99%